Investigating the Relationships Between Insulin Resistance, Cognitive Function and Alzheimer’s Disease Biomarkers and Exploring the Potential Benefits of an Insulin Mimetic. - Woodfield, Amy Marie (Curtin University, 2024)
Alzheimer’s Disease and Type 2 Diabetes share many common features, one of which is insulin resistance. This thesis explores how changes in insulin sensitivity and glucose metabolism impact brain function and Alzheimer??s biomarkers and assesses the benefits of anti-diabetic medications in the brain. Together, this provides insight into how peripheral changes in insulin sensitivity and glucose metabolism impact the brain and presents novel findings with an insulin-mimetic indicating potential modulation of the processing of amyloid-beta.